Electrical properties of Nb-DOPED Pb(Zr0.52Ti 0.48)O3 ceramics - Ketsuwan P. (2014)
The Pb(Zr0.52Ti0.48)O3 ceramics with 0.75, 1.0, 1.25 and 1.50%wt of Nb2O5 addition were prepared by a conventional mixed oxide technique. It was found that the average grain size of the ceramics decreased from 6 to 1 μm with increasing doping concentration to 1.5%wt. The room temperature dielectric constant and d33 reached maximum values of 1050 and 285 pC/N, respectively, at 1%wt Nb-doping. The electrical coercivity (Ec) of Nb-doped PZT decreased, while the polarization values increased, with increasing doping concentration. Most importantly, this study shows that Nb2 O5-doped PZT ceramics exhibits soft piezoelectric and enhanced ferroelectric behaviors, and the optimum properties can be obtained using suitable doping concentration. © 2009 World Scientific Publishing Company.